Direct Electrochemistry and Electrocatalysis of Horseradish Peroxidase Immobilized in a DNA/Chitosan-Fe(3)O(4) Magnetic Nanoparticle Bio-Complex Film - Gu, Tingting (Materials (Basel), 2014)
A DNA/chitosan-Fe(3)O(4) magnetic nanoparticle bio-complex film was constructed for the immobilization of horseradish peroxidase (HRP) on a glassy carbon electrode. HRP was simply mixed with DNA, chitosan and Fe(3)O(4) nanoparticles, and then applied to the electrode surface to form an enzyme-incorporated polyion complex film. Scanning electron microscopy (SEM) was used to study the surface features of DNA/chitosan/Fe(3)O(4)/HRP layer. The results of electrochemical impedance spectroscopy (EIS) show that Fe(3)O(4) and enzyme were successfully immobilized on the electrode surface by the DNA/chitosan bio-polyion complex membrane. Direct electron transfer (DET) and bioelectrocatalysis of HRP in the DNA/chitosan/Fe(3)O(4) film were investigated by cyclic voltammetry (CV) and constant potential amperometry. The HRP-immobilized electrode was found to undergo DET and exhibited a fast electron transfer rate constant of 3.7 s(−1). The CV results showed that the modified electrode gave rise to well-defined peaks in phosphate buffer, corresponding to the electrochemical redox reaction between HRP(Fe((III))) and HRP(Fe((II))). The obtained electrode also displayed an electrocatalytic reduction behavior towards H(2)O(2). The resulting DNA/chitosan/Fe(3)O(4)/HRP/glassy carbon electrode (GCE) shows a high sensitivity (20.8 A·cm(−2)·M(−1)) toward H(2)O(2). A linear response to H(2)O(2) measurement was obtained over the range from 2 μM to 100 μM (R(2) = 0.99) and an amperometric detection limit of 1 μM (S/N = 3). The apparent Michaelis-Menten constant of HRP immobilized on the electrode was 0.28 mM. Furthermore, the electrode exhibits both good operational stability and storage stability.